Epratuzumab modulates B-cell signaling without affecting B-cell numbers or B-cell functions in a mouse model with humanized CD22 - Özgör, Lamia; Brandl, Carolin; Shock, Anthony; Nitschke, Lars (European Journal of Immunology, 2016)
Treatment of systemic lupus erythematosus patients with epratuzumab (Emab), a humanized monoclonal antibody targeting CD22, leads to moderately reduced B-cell numbers but does not completely deplete B cells. Emab appears to induce immunomodulation of B cells, but the exact mode of action has not been defined. In the present study, we aimed to understand the effects of Emab on B cells using a humanized mouse model (Huki CD22), in which the B cells express human instead of murine CD22. Emab administration to Huki CD22 mice results in rapid and long-lasting CD22 internalization. There was no influence on B-cell turnover, but B-cell apoptosis ex vivo was increased. Emab administration to Huki CD22 mice had no effect on B-cell numbers in several lymphatic organs, nor in blood. In vitro exposure of B cells from Huki CD22 mice to Emab resulted in decreased B-cell receptor (BCR) induced Ca2+ mobilization, whereas B-cell proliferation after Toll-like receptor (TLR) stimulation was not affected. In addition, IL-10 production was slightly increased after TLR and anti-CD40 stimulation, whereas IL-6 production was unchanged. In conclusion, Emab appears to inhibit BCR signaling in a CD22-dependent fashion without strong influence on B-cell development and B-cell populations.
Keywords: Antibody therapy; B-cell differentiation; B-cell signaling; Systemic lupus erythematosus